2020
DOI: 10.3390/jcm9082492
|View full text |Cite
|
Sign up to set email alerts
|

Imaging in Primary Sjögren’s Syndrome

Abstract: Primary Sjögren’s syndrome (pSS) is a systemic autoimmune disease characterized by dysfunction and lymphocytic infiltration of the salivary and lacrimal glands. Besides the characteristic sicca complaints, pSS patients can present a spectrum of signs and symptoms, which challenges the diagnostic process. Various imaging techniques can be used to assist in the diagnostic work-up and follow-up of pSS patients. Developments in imaging techniques provide new opportunities and perspectives. In this descriptive revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 113 publications
(143 reference statements)
1
42
0
3
Order By: Relevance
“…Primary Sjögren's syndrome is a systemic autoimmune disease characterized by aberrant activation of immune responses and lymphocytic infiltration of the salivary and lacrimal glands, leading to xerostomia and xerophthalmia [87,88]. Recent studies have reported that UCMSCs alleviate the related symptoms via mediating the functions of T17 cells, Treg cells, T follicular helper (Tfh) cells, and macrophages.…”
Section: Primary Sjögren's Syndromementioning
confidence: 99%
“…Primary Sjögren's syndrome is a systemic autoimmune disease characterized by aberrant activation of immune responses and lymphocytic infiltration of the salivary and lacrimal glands, leading to xerostomia and xerophthalmia [87,88]. Recent studies have reported that UCMSCs alleviate the related symptoms via mediating the functions of T17 cells, Treg cells, T follicular helper (Tfh) cells, and macrophages.…”
Section: Primary Sjögren's Syndromementioning
confidence: 99%
“…In contrast, other studies have suggested that hypoechogenic areas reflect the level of damage of the glands. These discrepancies can be explained by differences in patient characteristics between cohorts [reviewed in van Ginkel et al ( 62 )].…”
Section: Ocular and Salivary Assessmentmentioning
confidence: 99%
“…It has recently been shown that imaging techniques can assist in the diagnosis of pSS, and in the assessment of the activity and progression of the disease. Furthermore, many imaging techniques have been evaluated as fundamental tools in diagnosis and staging of pSS-associated SGs lymphoma [ 22 ].…”
Section: Imaging and Parotid Swellingmentioning
confidence: 99%
“…Multimodal MRI examination (functional MRI, dynamic contrast-enhanced MRI, diffusion-weighted imaging, and apparent diffusion coefficient calculation) can increase differentiation accuracy of parotid lesions [ 53 , 54 , 55 ]. Although benign and malignant lesions of the SGs often appear similar, with overlapping and non-specific features in MRI, the high spatial resolution and fine characterization of deeper anatomical structures make MRI an imaging technique that can be useful in some cases for diagnostic guidance and local staging of pSS-associated SGs lymphoma [ 22 , 56 ]. Recently, as SGs features in MRI showed concordance with salivary glands ultrasound (SGUS), SGUS might represent a more accessible alternative for pSS assessment both in the diagnostic iter [ 22 ] and in guiding the histological sampling of suspicious lesions.…”
Section: Imaging and Parotid Swellingmentioning
confidence: 99%
See 1 more Smart Citation